Score [videorecording (DVD)] - Schrader, Matt, 1988-; Zimmer, Hans; Cameron, James, 1954-; Elfman, Danny; Jones, Quincy, 1933-; Williams, John, 1932- (Gravitas Ventures, 2017)
Documentary bringing Hollywood's elite composers together to give viewers a privileged look inside the musical challenges and creative secrecy of the world's most international music genre: the film score. Features interviews with nearly 60 composers, directors, orchestrators, studio musicians, producers, recording artists, studio executives, agents, and journalists.